Correlation between Morality and Religion in Ukrainian Society: Productive Ideas in German Idealism for Modern Consideration - Vadym Tytarenko (Ukrainian Policymaker, 2018)
Kant’s and Hegel’s ways to resolve the problem of correlation between the morality and religion at first glance seem to be opposite. Such opinion is evidenced by Hegel’s statements in which he puts himself into the opposition to Kant and demonstrates his own theoretical and methodological superiority. Many scholars of German Idealism support such opinion. But in spite of such radical alternativeness, in author’s opinion, it is possible to discover some mutual and non-contradicting positions of Kant and Hegel on the issue of correlation between the morality and religion. The purpose of this article is a comparison of the Kant’s and Hegel’s ways to resolve the problem of correlation between the morality and religion in order to discover the moments of complementarity in these extremely alternative philosophical systems. The results of this inquiry can be fruitfully assembled and used by the modern Ukrainian political and social science for resolving of this problem within the modern Ukrainian society. To achieve this purpose, it is necessary: a) to analyze and compare the general methodology used by Kant and Hegel in their philosophical systems; b) to conduct a comparison of their doctrines on morality, religion, and their correlation; c) to carry out a research in order to discover how Kant’s and Hegel’s theoretical and practical models, as well as achieved conclusions, can be fruitfully applied in the modern comprehension of the problem of correlation between the morality and religion.